2016
DOI: 10.1287/mnsc.2015.2294
|View full text |Cite
|
Sign up to set email alerts
|

A Reconsideration of Gender Differences in Risk Attitudes

Abstract: This paper reconsiders the wide agreement that females are more risk averse than males. We survey the existing experimental literature, finding that significance and magnitude of gender differences are task-specific. We gather data from 54 Holt and Laury (2002) replications, involving more than 7000 subjects. Gender differences appear in less than 10% of the studies, and are significant but negligible in magnitude once all the data are pooled. We exclude that this result is driven by noisier HL data. Gender di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(94 citation statements)
references
References 114 publications
8
86
0
Order By: Relevance
“…Two subjects were undecided between two of the integers, so we drop them from the analysis. 15 However, Crosetto and Fillipin (2013) find that gender risk-preference differences appear only when the task is more likely to trigger loss aversion; Filippin and Crosetto (2014) find that these differences are smaller with the Holt-Laury task.…”
Section: Discussionmentioning
confidence: 99%
“…Two subjects were undecided between two of the integers, so we drop them from the analysis. 15 However, Crosetto and Fillipin (2013) find that gender risk-preference differences appear only when the task is more likely to trigger loss aversion; Filippin and Crosetto (2014) find that these differences are smaller with the Holt-Laury task.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we complement the BMI index with an indicator that captures the quality of diet and nutrition behaviour -HEI -proposed by the US Department of Agriculture (Fischbacher, 2007;Filippin & Crosetto, 2014;Flegal et al, 2005 ). The HEI is currently considered the most advanced and complete measure of nutritional balance and quality of diet.…”
Section: Hei Health Indexes and Control Variablesmentioning
confidence: 99%
“…This renders the HEI a global measure of how far away from an "individually optimal" nutritional balance the actual diet is (Fischbacher, 2007;Filippin & Crosetto, 2014 ).…”
Section: Hei Health Indexes and Control Variablesmentioning
confidence: 99%
“…Dohmen et al (2007) echo this sentiment by claiming that "Risk and uncertainty play a role in almost every important economic decision" (p. 522), although Filippin and Crosetto (2014) in completing a detailed statistical analysis of microdata as well as a thorough analysis of the experimental literature, concluded that although gender differences are statistically significant, the effect size tends to be small in terms of economic outcomes. In an examination of how gender pertains to risk preferences in the experimental economics literature findings have also included that "women are more risk averse than men in the vast majority of environments and tasks" (Croson & Gneezy 2009, p. 449), consistent across lab experiments ISSN 2162-4860 2017 and experiments conducted in the field.…”
Section: Literature Reviewmentioning
confidence: 99%